EKSISTENSI TOKOH DALAM NOVEL SURAT KECIL UNTUK TUHAN KARYA AGNES DAVONAR - Siti Nur Farahin; Syafrial Syafrial; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is entitled Existence of Characters in the Novel of Small Letters to God by Agnes Davonar. This study aims to describe the existence of a character in the novel Letter to God by Agnes Davonar. The data in this research are qualitative data in the novel of Small Letters for God by Agnes Davonar relating to the object of research. Techniques of collecting data by means of collecting data that is documentation of the library, that is by reading the novel Letter to God, in the documentation of the study materials read and studied carefully to obtain research data. To get the result of research, researcher do check by using triangulation technique. Based on the results of research, the results obtained that in the novel Little Book to God by Agnes Davonar there are values of existence, whether it is aesthetic existence, ethical existence, and religious existence. Aesthetic existence is the ability of a person to maintain his existence by hating something excessive, belittling the norms and lovers of the lust of the world. Ethical existence is a stage that prioritizes one's perspective on his life and usually begins to sincerely live his life over what happens by observing the norms of life. Furthermore, religious existence is the return of man to God or his beliefs each with a way of life in accordance with the teachings of God. However, only a few figures have the value of existence in him, this is because the number of occurrences of the most in the novel compared with other figures. It can be concluded that Based on the kind of existence in a person, there are some things that must be considered is how to deal with problems in life until the end point of completion and still maintain the value of existence in oneself without having to lose that existence.Keywords: Existence, character, novel, Little Letter to God